1992
DOI: 10.1021/j100202a092
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of alkyl and fluoroalkyl radicals with nickel, iron, and manganese porphyrins

Abstract: The reactions of alkyl (CH,, C~HS, n-CJI9, CHZCOZ-, CH(C02-)2, CHzCN) and fluoroalkyl (CF,, CF2CI) radicals with nickel, iron, and manganese porphyrins (P) have been studied by radiolytic techniques in various solvents. All the radicals (R) react with Fe"P to form R-Fe"' P with a stable F t C bond. These products are oxidized by O2 to FelIIP. Althou h yield stable products. Reactions of alkyl radicals with NiIP result in unstable R-NinP products (tl 2 several seconds) that eventually yield NiIIP. Reactions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The formation of transients containing FeϪalkyl bonds is analogous to the formation of transient complexes in the reaction of alkyl radicals with iron() complexes, [18] and other low valent transition metal complexes, [16] in homogeneous solutions.…”
Section: Formation Of Alkanes During the Dissolution Of Analytical Mementioning
confidence: 99%
“…The formation of transients containing FeϪalkyl bonds is analogous to the formation of transient complexes in the reaction of alkyl radicals with iron() complexes, [18] and other low valent transition metal complexes, [16] in homogeneous solutions.…”
Section: Formation Of Alkanes During the Dissolution Of Analytical Mementioning
confidence: 99%
“…At −1.0 V vs Ag/Ag + , the Mn­(III), present at open circuit conditions, was completely converted Mn­(II), as evidenced by the shift of the Soret band to 442 nm (Figure c) . Ligand-based reductions in porphyrins are typically accompanied by changes at longer wavelengths, indicating that the reduction was solely metal-centered. , Tracking the ratio of the Mn­(III) to Mn­(II) Soret bands revealed the redox potential of the Mn to be centered at −0.8 V (Figure d).…”
Section: Results and Discussionmentioning
confidence: 94%
“…42 Ligand-based reductions in porphyrins are typically accompanied by changes at longer wavelengths, indicating that the reduction was solely metalcentered. 43,44 Tracking the ratio of the Mn(III) to Mn(II) Soret bands revealed the redox potential of the Mn to be centered at −0.8 V (Figure 2d).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Fuhrhop et al [9] characterized Mn(P) − as a manganese(II) radical anion, as did Kelly and Kadish [10] and Boucher and Garber [11]. Additional information confirming the radical anion structure was provided by Guldi et al [12], who observed a broad absorption band around 770 nm, which is characteristic of porphyrin π-radical anions. On the other hand, DFT calculations by Liao and Huang [13] predicted a Mn(I) structure for manganese porphine.…”
Section: Introductionmentioning
confidence: 84%